A Critical Analysis of the Integration of Humanistic Philosophical Values in Islamic Education: Between the Ethics of Empathy and the Rigidity of Dogma - Hanifatun Jamil; Ikenna Livinus Umeanolue; Yasin Adam (At-Ta'lim : Media Informasi Pendidikan Islam, 2025)
ENGLISH: A Critical Analysis of the Integration of Humanistic Philosophical Values in Islamic Education: Between the Ethics of Empathy and the Rigidity of DogmaObjective: This study critically examines the integration of humanistic philosophical values into Islamic education by highlighting the tension between the ethics of empathy and the rigidity of dogmatic instruction. Method: This research method uses critical-hermeneutic analysis, data collection using literature documents (textbooks), data analysis with hermeneutic interpretation, and ideological evaluation. Results: Although universal humanistic values align with Islamic teachings (ihsan and 'adl), the religious education curriculum remains normative and formal, and has not yet optimally integrated the empathetic dimension. Conclusion: There is a dichotomy between the cognitive-formal approach to Islamic education in madrasahs and the social-empathetic approach in pesantren, reflecting the difference between academic aspects and character building and social empathy. Contribution: This study reinforces the paradigm of Islamic education that is transformative, contextual, civilized and relevant to the challenges of religious education in a pluralistic and complex society.INDONESIAN: Analisis Kritis Integrasi Nilai-nilai Pemikiran Filsafat Humanistik dalam Pendidikan Islam: Antara Etika Empati dan Keteguhan DogmaTujuan: Penelitian ini bertujuan untuk menganalisis secara kritis integrasi nilai-nilai filsafat humanistik dalam pendidikan Islam dengan menyoroti ketegangan antara etika empati dan keteguhan dogma. Metode: Metode penelitian ini menggunakan nalisis kritis-hermeneutik, pengumpulan data menggunakan dokumen literatur (buku teks), analisis data dengan interpretasi hermeneutis dan evaluasi ideologis. Hasil: Meskipun nilai humanistik universal sejalan dengan ajaran Islam (ihsan dan 'adl), kurikulum pendidikan agama masih normatif-formal dan belum mengintegrasikan dimensi empatik secara optimal. Kesimpulan: Terdapat dikotomi antara pendekatan pendidikan Islam kognitif-formal di madrasah dan sosial-empatik di pesantren, yang mencerminkan perbedaan antara aspek akademik dan pembentukan karakter serta empati sosial. Kontribusi: Penelitian ini memperkuat paradigma pendidikan Islam yang transformatif, kontekstual, dan berkeadaban, serta relevan untuk tantangan pendidikan agama di masyarakat plural dan kompleks.